Kisah Nabi Yusuf dalam Al-Qur’an dan Alkitab: Suatu Pendekatan Intertekstual Julia Kristeva - Rizal Faturohman Purnama (Islamic Religious Education Departement, 2021)
This article discusses the story of The Prophet Yusuf in the Qur'an. As the story is contained in the Qur'an and the Bible, from both books the story of Yusuf tells about four things. First, the story of Yusuf dreaming, Secondly, the tragedy of Yusuf being banished. Third, the story of Yusuf and Imara'ah Al-'aziz. Fourth, the story of Yusuf’s imprisonment. Therefore, this story becomes important to be examined more deeply aimed at finding the differences of the two scriptures about the story of yusuf. Therefore, the approach used is intertekstual initiated by Julia Kristeva who seeks to compare the two. Thus, this study found many differences, in terms of dominant in each fragment. The most basic difference between the two is in terms of the theme to be raised, the song of Joseph in the Qur'an themed on the teachings of Tawhid, while in the Bible themed on power